2020
DOI: 10.3390/genes11091075
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulate Intestinal Immunity and Gut Microbiota for Gastrointestinal Health: A Comprehensive Review

Abstract: MicroRNAs are small non-coding RNAs regulating gene expression at the post-transcriptional level. The regulation of microRNA expression in the gut intestine is gradually recognized as one of the crucial contributors of intestinal homeostasis and overall health. Recent studies indicated that both the microRNAs endogenous in the gut intestine and exogenous from diets could play influential roles in modulating microbial colonization and intestinal immunity. In this review, we discuss the biological functions of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 149 publications
(158 reference statements)
1
32
0
1
Order By: Relevance
“… 35 Alternatively, some studies have shown that miRNA expression can be altered by several dietary agents taken by the host 36 and in turn, such regulated miRNA can modulate the gut microbiome, and dietary agents may directly influence the microbiome as well. 37 Deregulation of miRNA expression and dysbiosis of the gut intestinal microbiota are strongly interconnected, leading to the occurrence of several diseases in the host, including cancers.
Figure 1 Inter-domain communications occur among host-gene expression, host miRNA expression, and host gut microbiome.
…”
Section: Inter-domain Communications Between the Gut Microbiome And Host Mirnas In Cancermentioning
confidence: 99%
“… 35 Alternatively, some studies have shown that miRNA expression can be altered by several dietary agents taken by the host 36 and in turn, such regulated miRNA can modulate the gut microbiome, and dietary agents may directly influence the microbiome as well. 37 Deregulation of miRNA expression and dysbiosis of the gut intestinal microbiota are strongly interconnected, leading to the occurrence of several diseases in the host, including cancers.
Figure 1 Inter-domain communications occur among host-gene expression, host miRNA expression, and host gut microbiome.
…”
Section: Inter-domain Communications Between the Gut Microbiome And Host Mirnas In Cancermentioning
confidence: 99%
“…Connecting the heritability and the environmental influence, unique microRNA (miRNA) expression profile signatures have been associated with IBD pathogenesis. In this regard, both endogenous gut miRNAs and exogenous miRNAs from diet could actively modulate microbial colonization and intestinal immunity [ 84 ]. Thus, gut microbiota in IBD patients differs from healthy individuals, as it is characterized by a reduced diversity, increased abundance of Enterobacteriaceae and reduced abundance of Firmicutes and Bacteroidetes phyla [ 85 ].…”
Section: Limosilactobacillus Fermentummentioning
confidence: 99%
“…Non-traditional signaling pathways involving micro-RNA (miRNA) also influence CHD and the microbiome [108,109]. There are miRNA's associated with intestinal dysbiosis, barrier dysfunction, and CHD.…”
Section: Organisms Withinmentioning
confidence: 99%